Answer:
![f^(-1)(x)=\pm (√(x+4) )/(3)](https://img.qammunity.org/2020/formulas/mathematics/high-school/sa60p678ngdbus800a11ok9kva9bt7ix4j.png)
Explanation:
In order to find the inverse of
we need to follow the next steps:
Step 1: Solve for x
Add 4 to both sides:
![y+4=9x^2-4+4\\y+4=9x^2](https://img.qammunity.org/2020/formulas/mathematics/high-school/9bw3qiws61am310kz2w2oc68w2dmkxlkuy.png)
Divide by 9 from both sides:
![(y+4)/(9)=(9x^2)/(9) \\(y+4)/(9)=x^2](https://img.qammunity.org/2020/formulas/mathematics/high-school/pkwbd3jqo4jmpcetd8fl2dnhujcozr7xqs.png)
Square root from both sides:
![√(x^2)=\pm \sqrt{(y+4)/(9)} \\x=\pm (√(y+4) )/(3)](https://img.qammunity.org/2020/formulas/mathematics/high-school/6t5izbx71w6y1ehcedx3t6ammbf2i85k6i.png)
Step 2: Replace every x with a y and replace every y with an x.
![y=\pm (√(x+4) )/(3)](https://img.qammunity.org/2020/formulas/mathematics/high-school/6ahyhnscapkkqllhx3sv7qz8i3py5rovdc.png)
So:
![f^(-1)(x)=\pm (√(x+4) )/(3)](https://img.qammunity.org/2020/formulas/mathematics/high-school/sa60p678ngdbus800a11ok9kva9bt7ix4j.png)
Step 3: Verify your work by checking that:
![(f \hspace{3}o\hspace{3}f^(-1))(x)=x\\(f^(-1)\hspace{3}o\hspace{3}f)(x)=x](https://img.qammunity.org/2020/formulas/mathematics/high-school/gu1tpbwzgbghwec697dy7s8hsk7ebbcp01.png)
![(f \hspace{3}o\hspace{3}f^(-1))(x)=x=9((√(x+4) )/(3))^2 -4=x+4-4=x](https://img.qammunity.org/2020/formulas/mathematics/high-school/j1ndgwwe1o3gfut3vy7kfmycxaiapm1jkq.png)
![(f^(-1)\hspace{3}o\hspace{3}f)(x)=x=(√(9x^2-4+4) )/(3) =(√(9x^2) )/(3) =(3x)/(3) =x](https://img.qammunity.org/2020/formulas/mathematics/high-school/nzjoevlqrb0ti2diq6dxp1ucrok6n3upr2.png)